ADDICTION TO DIGITAL TEHNOLOGY, A PROBLEM OF CONTEMPORARY SOCIETY (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Addiction to Digital Tehnology, A Problem of Contemporary Society.The amount of time spent on digital technology has increased considerably, especially among young people, who spend up to half their day using technology. Digital technology is beneficial as long as it is not overused and does not take over an individual’s entire existence. Once established, digital addiction has long-term negative effects on a person’s life and requires specialized treatment.The study aims to analyze various aspects of digital technology use among young people, with a focus on the effects it can have. The participants in the study were pupils and students (bachelor and master) studying in Bucharest, but living both in Bucharest and in different parts of the country, in rural and urban areas. The qualitative research was carried out in Bucharest and consisted of 27 semi-structured interviews and three focus groups.Over time, the excessive use of digital technology can lead to major changes in the health and behavior of young people: reduced communication skills, a tendency to isolate themselves, increased fatigue, anxiety, problems with attention, irritability, headaches, excessive eye strain and even visual impairment, insomnia, sadness, depression, low self-esteem, superficial assimilation of information, problems with memory and/or language, etc. Digital technology addiction can therefore be considered a public health problem with disastrous long-term effects.